Penerapan Inovasi Pelayanan Berbasis E-Government terhadap Peningkatan Pelayanan Publik pada Kantor Wilayah Direktorat Jenderal Kekayaan Negara (DJKN) Banten - Ratnawati; Benny Sigiro (Jurnal Ilmiah Administrasita', 2025)
Service quality and user satisfaction are essential elements that must not be overlooked but instead prioritized in modern public governance, particularly within government institutions that oversee wide operational areas such as the Regional Office of the Directorate General of State Assets (Kanwil DJKN) Banten. This study aims to examine the implementation of e-government–based public service innovations in improving service user satisfaction. The method used in this research is a literature study, utilizing secondary data from various references such as scientific journal articles, government regulations, and other relevant documents related to the research topic. The findings indicate that public service innovation plays a crucial role in shaping a positive public perception of bureaucracy while promoting institutional efficiency and accountability. At Kanwil DJKN Banten, the implementation of e-government–based service innovations such as “APT Online,” “Solider Zone,” “SIAP,” and “SIBINA” has significantly contributed to increasing user satisfaction through faster service delivery, improved accessibility, and transparency in service processes. The implications of this research highlight the importance of strengthening information technology capabilities and ensuring continuous technological development to expand service outreach and enhance bureaucratic responsiveness in line with the increasing complexity of public needs and interests.